Medieval Hunting as Training for War Insights for the Modern Swordsman - Richard Swinney; Scott Crawford (Bern Open Publishing, 2021)
Since antiquity, hunting (the pursuit of large game with dogs, swords, spears and bows) has been advocated as the best means of training men for war. The cognitive, psychological and physical demands of hunting in this fashion develop a fundamentally different skill set from that of standard modern Western Martial Arts training. Still legal in the United States, hunting wild boar employing medieval weapons and methods provides insights into swordsmanship readily available nowhere else.